The Steep Road to Renewal of Islamic Law through Maqasid Values - Faishal Nur, Ahmad; Effendi, Orien (State of Islamic Institute Langsa, 2023)
Islamic law is substantively derived from the teachings of Islam. As a religious teaching, Islamic law comes from Allah and is extracted directly from the Qur'an and al-Sunnah. This Islamic law is then considered as something sacred and cannot be changed. This thought then makes Islamic law rigid and even static and ultimately not ready to answer various problems, even though Islamic law in the reality of human life requires continuous dynamization and development. The dynamization of Islamic law will be achieved when there is a dialectic between text and reality, thus always finding new innovations in the context of legal discovery, the goal is to achieve benefit. Using an analytical study through library research based on primary and secondary data with a juridical normative approach. This research shows that there are still Muslims who consider the sacredness of classical Islamic law as an absolute truth that cannot be changed, the attitude of some of these circles makes Islam feel foreign to the environment that surrounds it. The situation is exacerbated when they do not fully accept the renewal of Islamic law such as the presence of contemporary maqashid concepts or values.